Evolution of the magmatic-hydrothermal system at Lastarria volcano (Northern Chile) between 2006 and 2019: Insights from fluid geochemistry - Layana, Susana; Aguilera, Felipe; Inostroza, Manuel; Tassi, Franco; Wilkes, Thomas Charles; Bredemeyer, Stefan; González, Cristóbal; Pering, Tom David; McGonigle, Andrew John Samuel (Frontiers in Earth Science, 2023)
Gas chemical surveys and measurements of SO2 emission rates performed in the past (2006-2019) at Lastarria volcano in Northern Chile have revealed a persistent increment of magmatic sourced gas emissions since late November 2012, following a 13 years period of intense ground surface uplift. Lastarria-Cordón del Azufre area (also known as Lazufre) has undergone large scale ground deformation (up to 3.5 cm/yr) in the period 1998-current, hinting at the inflation of a deep magmatic reservoir (~10 km) fed by magmatic volatiles ascending from depth. Uplift of the area later (in the period 2000-2008) further was accompanied by a weaker (9 mm/yr) and more localized shallow-sourced uplift (<1 km depth) below the fumarolic area at Lastarria volcano suggesting temporary inflation of an over-pressured hydrothermal system. In this work, we provide new insights into the gas-chemical evolution of Lastarria’s fumarolic discharges obtained from direct sampling (2006-2019) and SO2 emission rates using UV camera and DOAS instruments (2018-2019) and link these to pre-existing information on ground deformation (1998-2016) in order to determine the origin of observed degassing and ground deformation processes. We revise the four mechanisms originally proposed as alternatives by Lopez et al. (2018) to explain the changes observed in the fluid geochemistry and ground deformation between 2009 and 2012, in order to explain major changes in gas-geochemistry over an extended period between 1998 and 2019. We hypothesize that a continuous sequence of processes explains the evolution in the fluid geochemistry of fumarolic discharges. Two mechanisms are responsible of the changes in the gas composition during the studied period, corresponding to a (1) deep magma chamber pressurized by volatile exsolution (1998?-2020), which is responsible of the large-scale deformation at Lazufre area; followed by (2) a crystallization-induced degassing (2001?-2020) and pressurization of the hydrothermal system (2003-early November 2012?), where the former process induced the changes in the gas composition from hydrothermal-dominated to magmatic-dominated, whereas the last produced the small-scale deformation at Lastarria volcano. As a consequence of the changes in the gas composition strongly dominated by magmatic volatiles, it was produced the acidification (late November 2012-2020?) and depletion (2019-2020) of the hydrothermal system.